Potensi dan Strategi Pengembangan Peternakan Sapi Potong di Kabupaten Rokan Hulu Provinsi Riau - Doni Doni; Khasrad Khasrad; Arfa’i Arfa’i (Universitas Batanghari Jambi, 2023)
In the context of developing beef cattle, it is necessary to look at the existing potential and the strategies used. The purpose of this study is to analyze the potential for beef cattle development in the district of Rokan upstream and to formulate a development strategy in the future. This research is descriptive qualitative, the data used are primary data and secondary data through interviews and direct observation. This research was carried out in three stages. Stage one; Identification and analysis of beef cattle development potential. Stage two; Analysis of beef cattle business in the central area. The third stage is formulating a strategy. To formulate a strategy using a SWOT analysis followed by a QSPM analysis in determining the priority of beef cattle development strategies. The results showed that there were seven sub-districts that became the basis for the development of beef cattle, namely: Bangun ancient sub-districts, Kecepatan upstream, Rambah samo, Rambah downstream, Rokan IV Koto, Pendalian IV Koto, Tandun and Pagaran tapah. The value of the capacity for increasing the population of ruminant livestock (KPPTR) is 33,724,02 ST. The priority strategies in beef cattle development are 1) Determination of livestock areas through regional regulations, 2) Encouraging groups to develop livestock nurseries, 3) Encouraging the growth of financial institutions to increase farmer capital, 4) Improving the marketing system, 5) Improving livestock breeding, 6) Livestock development with an integrated system, 7) Land optimization, 8) Encouraging the growth of financial institutions, 9) Conducting farmer training, 10) Increasing farmer's capital, 11) Group counseling and 12) Group development in beef cattle business efficiency.